45th AIAA Fluid Dynamics Conference 2015
DOI: 10.2514/6.2015-2633
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of 3-D Stall Cells on 2-D Airfoil

Abstract: The present work aims to identify and quantify underlying physics behind the formation of three-dimensional stall cell using oil flow visualization and stereoscopic particle image velocimetry (SPIV) on a two-dimensional NACA 0015 airfoil. The three dimensional structures were explored at various angles of attack ( = 14 o to 18 o ) and Reynolds numbers (Re c = 1.62•10 5 to 4.2•10 5 ). Surface oil flow visualization was used to qualitatively identify the stall cells and resolve associated equivalent near surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…5, the separated flow past thick FB airfoils is three-dimensional (3D) and coherent structures known as stall cells form. Stall cells are large-scale 3D structures of separated flow that consist of two counter-rotating vortices [15][16][17][18][19] that form on the suction side of airfoils experiencing TE stall. 20 Additionally, the literature suggests that in high Re number experiments and simulations, 13,[21][22][23][24] reduced drag values are observed just before stall.…”
Section: Introductionmentioning
confidence: 99%
“…5, the separated flow past thick FB airfoils is three-dimensional (3D) and coherent structures known as stall cells form. Stall cells are large-scale 3D structures of separated flow that consist of two counter-rotating vortices [15][16][17][18][19] that form on the suction side of airfoils experiencing TE stall. 20 Additionally, the literature suggests that in high Re number experiments and simulations, 13,[21][22][23][24] reduced drag values are observed just before stall.…”
Section: Introductionmentioning
confidence: 99%
“…Boiko et al (1996) also noted that similar structures, in the form of both unsteady and quasi-steady vortex phenomenon, had been described in the literature for years over cylinders as well as airfoil. Observations of these structures were made using tufts (Humphreys, 1960;Broeren & Bragg, 2001;Manolesos & Voutsinas, 2014a) and via oil flow visualization (Gregory et al, 1971;Winkelmann & Barlow, 1980;Weihs & Katz, 1983;Schewe, 2001;DeMauro et al, 2015;. Disotell (2015) noted that stalls cell generally occur only on bodies that experience trailing-edge separation.…”
mentioning
confidence: 98%
“…They found that, under these conditions, three types of vortical structures are present in the flow: 1) Stall cell vortices that start normal to the surface and then bend to align with the free stream, where their focal points are within the separation line, 2) A separation line vortex, and 3) A trailing edge line vortex, which grows significantly near the center of the stall cell. DeMauro et al (2015) and have focused on comparing oil flow visualization and SPIV results over different aspect ratio NACA0015 airfoils. They also used zig-zag tape near the leading edge of the airfoil to induce stall cells in circumstances where the flow would otherwise exhibit 2-D separation.…”
mentioning
confidence: 99%